Caça de animais silvestres nas reservas de desenvolvimento sustentável Mamirauá e Amanã - Joao Valsecchi do Amaral (2012)
This study aims to elucidate some central questions about the use of wildlife in two protected areas in the Brazilian Amazon. The work was carried out at Mamirauá and Amana Sustainable Development Reserves, and had as a general objective to generate information for the conservation and management of hunted species in the Amazon. The thesis is presented as four scientific articles. Chapter one describes the hunting patterns found in the reserves, determining which species are the most important locally and evaluating possible spatial and temporal variations of the activity. Chapter two describes the techniques, means of transport, and hunting tools used by riverine hunters in the middle Solimões river region. Chapter three describes paca hunting in the Amanã Reserve, and tests the relation between hunting levels with lunar cycles. A productivity analysis is used to evaluate the impacts of hunting on the populations of paca and an alternative monitoring method is discussed. Finally, chapter four characterizes hunting of four feline species that occur in both Reserves: jaguar (/Panthera onca/), puma (/Puma concolor/), ocelot (/Leopardus pardalis/) and margay (Leopardus wiedii), and generate an estimate of the numbers of animals hunted for each species.